Produção e caracterização de laminados biodegradáveis e antimicrobianos para embalagens de alimentos - Pizzoli, Ana Paula de Oliveira (2014)
Due to the growing demand for replacement of the usual packaging materials for biodegradable as well as the need to maintain food safety during storage, the development of bioactive biodegradable packaging becomes important. In this work sheets were produced by extrusion and calendaring process using blends of poly(L-lactic acid) (PLLA), thermoplastic starch (TPS) and gelatin . The process is presented as a viable way to produce blends of PLLA/TPS/gelatin with interesting functional properties and homogeneous appearance. The addition of gelatin in different proportions (1, 3 and 5% related to TPS) showed a significant difference in the solubility test results, the water vapor permeability (WVP) and water sorption isotherms due to gelatin hydrophilicity. Furthermore the incorporation of gelatin in the blend significantly affected the mechanical properties by reducing stiffness associated with incompatibility between PLLA, starch and gelatin, as shown by Scanning Electron Microscopy (SEM) micrographs. Silver nanoparticles (AgNPs) were synthesized for incorporation into the extruded sheets by the modified polysaccharide technique, where silver nitrate is reduced to metallic silver by D-glucose. The average diameter was determined by three techniques: Dynamic light scattering (DLS, 63 nm) by UV-Vis spectrophotometry (100 nm) and by analysis of SEM images (145 nm). With the analysis of FTIR was possible to detect interactions between the C = O groups of D-glucose oxidation byproducts, products of the reaction with silver nitrate. AgNPs presented effective antimicrobial action against the microorganisms: Bacillus cereus, Staphylococcus aureus, Pseudomonas aeruginosa, and Escherichia coli, and the Minimum Inhibitory Concentration equal to 1.17 µg/ml for E. coli (lower resistance) and 37.50 µg/ml for S. aureus (greater resistance). The extruded sheets were surface treated with the resulting solution from AgNPs synthesis and enzymatically crosslinked with transglutaminase. At the SEM images it was possible to verify that the treated laminates exhibited higher porosity due to moisture promoted by the treatment. The created porosity influenced significantly the results of the WVP and mechanical properties. There was an increase in vapor permeation and a reduction in all mechanical characteristics, particularly in Young's modulus due to the creation of tension concentration points. The isotherms showed adequate adjustment to GAB model (R2> 0.99). The antimicrobial activity of the laminates containing AgNPs was confirmed by the formation of inhibition zones against the microorganisms described above. Finally, the sheets produced have potential application as active packaging with antimicrobial and biodegradable properties for food.